The Sociology of People Food; a New Concept on The Root of People's Food Security (The Environmental Principles Approach) - Mortaza A Syafinuddin Hammada; Sennahati; Harifuddin Halim; Surahman Cinu; Qudratullah Hossein Mothahhari (PT FORMOSA CENDEKIA GLOBAL, 2022)
This study seeks to find other approaches to find solutions to people food problems. This study uses a qualitative approach through a process of observation and participatory research. The collection of data and information was carried out through a series of observations and extracting information from informants in the field using an open or unstructured interview sheet instrument. The study, hereinafter referred to as food sociology, in this paper confirms that people who have lost their food transformation pattern will find it difficult to achieve food security. Therefore, they are very close to food insecurity and crisis. A transformation process is needed, including diversifying food ingredients through a series of people's education processes to cultivate food diversification.